O presidencialismo de coalizão: o caso do Estado do Espírito Santo entre anos de 1991 a 1994 - Lima, Marcelo Siano (2011)
The dissertation discusses the construction of political and institutional relations between the Executive and legislative powers of the State of Espírito Santo, in the period between 1991 and 1994, generating a paradigm of Government whose constituent aspects are of interest to the State's political history. As the main protagonists of this whole plot I quote the then Governor of the State, Albuíno Cunha de Azeredo, and thirty parliamentarians who were part of the Legislative Assembly, assisted by a broad and complex set of actors and interests, entered into the historical context of changes that were from the consolidation of democratic political regime, the amendment of the constitutional system, the new economic dynamics and the new forms of representation of social interests. Special attention is devoted to the process of impeachment introduced in the legislature against the Governor Albuíno in 1993, because I consider it as the key element for the understanding of the disputes and games politicians among the protagonists of the whole plot historic object of this research. I'm worth of methodological frame of the story of the present time, and the theoretical perspective of presidential system of federalist coalition and “ultrapresidencialismo” to build this dissertation, to walk through the events, understand them and relate them.